Who controls your future: The convention on the rights of persons with disabilities from a service user focused perspective. (February 2020) - Newton-Howes, Giles; Gordon, Sarah
Although notions of personal autonomy are increasingly enshrined as the primary principle of ethical medical practice, psychiatry appears to have real difficulty in applying this. Notions such as compulsory treatment and mental health legislation serve to reinforce paternalism. This may not be in the interests of either the patient or the doctor. The Convention on the Rights of Persons with Disabilities (CRPD), although providing no new rights to mental health patients, has led to guidance as to what existing rights entail and how they should be applied. While service users were involved in the drafting of the Convention on the Rights of Persons with Disabilities, what is lacking is service user focused perspectives in the critique and debate that has ensued in response to the Convention on the Rights of Persons with Disabilities committee's informed guidance as to the correct interpretation of the rights. Furthermore, consideration of how to translate the rights into practice is also lacking. This co-produced viewpoint aims to contribute to this debate and provides a brief overview of a novel educational approach to translating the Convention on the Rights of Persons with Disabilities committee's guidance into clinical practice.